A functional assay for serum detection of antibodies against SARS‐CoV‐2 nucleoprotein. (29th July 2021) - Albecka, Anna; Clift, Dean; Vaysburd, Marina; Rhinesmith, Tyler; Caddy, Sarah L; Favara, David M; Baxendale, Helen E; James, Leo C
Abstract: The humoral immune response to SARS‐CoV‐2 results in antibodies against spike (S) and nucleoprotein (N). However, whilst there are widely available neutralization assays for S antibodies, there is no assay for N‐antibody activity. Here, we present a simple in vitro method called EDNA (electroporated‐antibody‐dependent neutralization assay) that provides a quantitative measure of N‐antibody activity in unpurified serum from SARS‐CoV‐2 convalescents. We show that N antibodies neutralize SARS‐CoV‐2 intracellularly and cell‐autonomously but require the cytosolic Fc receptor TRIM21. Using EDNA, we show that low N‐antibody titres can be neutralizing, whilst some convalescents possess serum with high titres but weak activity. N‐antibody and N‐specific T‐cell activity correlates within individuals, suggesting N antibodies may protect against SARS‐CoV‐2 by promoting antigen presentation. This work highlights the potential benefits of N‐based vaccines and provides an in vitro assay to allow the antibodies they induce to be tested. SYNOPSIS: The neutralizing titre of S‐antibodies produced in response to SARS‐CoV‐2 infection is easily measured, but there is no equivalent assay for N‐antibodies. Here we present a simple in vitro assay that quantifies the antiviral activity of N antibodies in SARS‐CoV‐2 convalescent sera. EDNA (electroporation‐based neutralization assay) exploits 'Trim‐Away' technology to deliver sera directly into cells prior to infection and qPCR measurement of viral neutralization. An EDNA‐based screen of health‐care workers reveals a threshold N titre for intracellular neutralization. Anti‐N antibodies neutralize SARS‐CoV‐2 infection intracellularly using TRIM21. A strong anti‐N neutralization response correlates with N‐specific T cell proliferation. Abstract : A new in vitro assay, EDNA, measures neutralizing activities of patient antibodies against coronaviral N protein, complementing available methods for evaluating antiviral activities of anti‐spike (S) protein antibodies.